A Lesson in Carefully Managing Resources: A Case Study from an Evaluation of a Music Education Program - Kristin A Hobson; Jason T Burkhardt (Journal of MultiDisciplinary Evaluation)
Background: A music education program with a goal of enhancing cognitive development of preschool-aged children enrolled in local preschools is evaluated by The Evaluation Center at Western Michigan University. The budget for the evaluation was small, and therefore presented several challenges to the evaluation team.